Kebermaknaan Kata pada Ungkapan Ndasmu dan Hidup Jokowi oleh Prabowo dalam Perspektif Analisis Wacana Kritis Norman Fairclough : The Meaning of Words in Prabowo's Expression ‘Ndasmu dan Hidup Jokowi’ (Your Head and Jokowi's Life) from the Perspective of Norman Fairclough's Critical Discourse Analysis - Faaza, Alfin; Waningyun, Prissilia Prahesta (Universitas Tidar, 2025)
This research analyses the use of the phrases ‘Ndasmu’ and ‘Hidup Jokowi’ in Prabowo Subianto's political speech through Norman Fairclough's Critical Discourse Analysis (AWK) perspective. The research aims to reveal power relations, ideological conflicts, and their impact on public opinion in the Indonesian political context. A qualitative method with a document study approach was applied to analyse data from news, speech videos, and social media responses. The results show that both phrases operate on three dimensions of AWK namely, (1) The text dimension, where ‘Ndasmu’ functions as a tool of delegitimising critics through sarcasm, while ‘Hidup Jokowi’ builds a narrative of continuity of power, (2) The discursive practice dimension, with the production and distribution of discourse in non-formal spaces triggering polarisation of interpretations, (3) The social context dimension, which confirms the influence of hierarchical Javanese culture and the dynamics of post-2024 post-election politics. The implications of the research reveal that the rhetoric has the potential to erode the quality of democracy through the reduction of critical dialogue space, increased polarisation, and the reproduction of power hegemony. This research recommends increasing people's critical literacy and the ethical responsibility of political actors in using language as an instrument of public communication.